Antioxidant, Anti-Tyrosinase, and Wound-Healing Capacities of Soy Protein Hydrolysates Obtained by Hydrolysis with Papaya and Cantaloupe Juices Showing Proteolytic Activity - Thi-Phuong Nguyen; Quang Thai Le; Mai Linh Thi Tran; Kim Nhung Ta; Khoa Thi Nguyen (Polish Journal of Food and Nutrition Sciences)
Purified and crude proteases have been broadly applied to obtain hydrolysates from soy protein isolate (SPI) with the improved functional and biological properties. However, the use of fruit juices containing native proteases to produce SPI hydrolysates with better bioactivities receives less attention. The present study attempted to investigate the ability of papaya ( Carica papaya ) and cantaloupe ( Cucumis melo ) juices in the hydrolysis of SPI and assess the antioxidant, anti-tyrosinase, and wound-healing activities of obtained hydrolysates. Our analysis showed that SPI was hydrolysed by papaya juice, at the juice to substrate ratio of 2.5:2 ( v/ w), with a degree of hydrolysis (DH) of approximately 11% after 4 h of treatment at 55ºC. A higher DH (about 26%) was obtained by the hydrolysis with cantaloupe juice at the same juice to substrate ratio and treatment conditions. Papain used at the enzyme to substrate ratio of 0.625:2 ( w/w ) broke down SPI in a similar DH as papaya juice at the juice to substrate ratio of 2.5:2 ( v/w ). The ABTS •+ -scavenging, • OH-scavenging and tyrosinase inhibitory capacities of SPI were lower than those of hydrolysates obtained by the treatment with papaya juice (IC 50 of 2.39, 7.17, and 32.07 μg/mL, respectively) and cantaloupe juice (IC 50 of 2.46, 6.93, and 30.49 μg/mL, respectively). An enhancement in ABTS •+ -scavenging, • OH-scavenging and anti-tyrosinase activities was also observed in the hydrolysate obtained by papain (IC 50 of 2.75, 17.85, and 117.80 μg/mL, respectively) compared to SPI. However, the increased level of the • OH-scavenging capacity of the hydrolysate obtained by papain was lower than that of the fruit juice-treated samples. Remarkably, the hydrolysates prepared from the hydrolysis with fruit juices accelerated the wound closure in human fibroblasts by estimately 1.5 times after 24 h of treatment while this property was not observed in the hydrolysate by papain. Our study data suggest the potential of SPI hydrolysates obtained by papaya and cantaloupe juices in the preparation of healthy food products.